“Breaking the Horizon of Expectation in the Poetry of Abū Tammām between al-Āmidī and al-Maʿarrī: Their Metaphors as a Model.” - daif allah, saaid. (El Omda in Linguistics and Discourse Analysis, 2018)
Classical critics were preoccupied with metaphor as the most prominent feature representing the poetic approach of Abū Tammām. They directed their criticism toward it because it was so abundant in his poetry. As a result, two groups emerged: the first was biased toward the ancients and rejected the idea of departing from traditional conventions, while the second supported Abū Tammām’s approach, seeing in it considerable innovation and creativity. Consequently, his poetry shocked its audience, both readers and listeners. His verse requires a particular type of reader who must exert a special interpretive effort. Among such readers, I have selected two important critics who approached Abū Tammām’s poetry through the lens of their cultural backgrounds: al-Āmidī and al-Maʿarrī. I have focused on how each of them dealt with the topic of metaphor through a comparative study.